THE OBSTACLES OF ENGLISH TEACHERS FACE IN INCREASING STUDENTS’ LEARNING MOTIVATION - Yeslika Bangun; Erika Sinambela (Jurnal Pendidikan dan Pengajaran (JUPEJA), 2026)
Teachers play a crucial role in achieving successful learning outcomes, significantly influencing the quality of education. This study aims to describe the obstacles faced by teachers in improving students' learning motivation in English language learning at SMP Negeri 1 Tigapanah. Using a descriptive qualitative research design, data were collected through interviews, observations, and documentation from English teachers. Data analysis involved reduction, presentation, and conclusion drawing, with validity checked through triangulation techniques. The findings reveal two main obstacles: family/parental factors and peer group influences. Despite these challenges, teachers actively employ various strategies to enhance student motivation.